El "Hortus philosophiae" como sistema de memoria local: El ejemplo del Congestorium - Ramos Grané, Marta (Cauriensia, 2023)
In the present work we aim to analyze the usage of the typical tree scheme of the Lullian tradition in the Congestorium artificiosae memoriae by Johannes Romberch (Venice, 1520). This Dominican author is the only treatise writer of his time who uses this diagram as a place for memory to order some content in the form of mnemonic images. In order to do that, we will observe the figure in which Romberch unfolds the scholastic hierarchy of knowledge, as well as its images and implications. Likewise, in the light of the Congestorium itself, we will point out the possible reasons that led its author to use such an unusual place in his discipline.